Advances in Cloud Physics and Weather Modification in China - Guo, Xueliang; Fu, Danhong; Li, Xingyu; Hu, Zhaoxia; Lei, Henchi; Xiao, Hui; Hong, Yanchao (Advances in atmospheric sciences, 2015)
The capabilities of cloud-resolving numerical models, observational instruments and cloud seeding have improved greatly over recent years in China. The subject of this review focuses on the main progresses made in China in the areas of cloud modeling, field observations, aerosol–cloud interactions, the effects of urbanization on cloud and precipitation, and weather modification.Well-equipped aircraft and ground-based advanced Doppler and polarized radars have been rapidly applied in cloudseeding operations. The combined use of modern techniques such as the Global Positioning System, remote sensing, and Geographical Information Systems has greatly decreased the blindness and uncertainties in weather-modification activities.Weather-modification models based on state-of-the-art cloud-resolving models are operationally run at the National Weather Modification Centre in China for guiding weather-modification programs.Despite important progress having been made, many critical issues or challenges remain to be solved, or require stronger scientific evidence and support, such as the chain of physical events involved in the effects induced by cloud seeding. Current important progresses in measurements and seeding techniques provide the opportunity and possibility to reduce these deficiencies. Long-term scientific projects aimed at reducing these key uncertainties are extremely urgent and important for weather-modification activities in China.